1995
DOI: 10.1002/jemt.1070300403
|View full text |Cite
|
Sign up to set email alerts
|

Organ culture of benign, aging, and hyperplastic human prostate

Abstract: Organ culture of the human prostate began in the 1970s and was modeled after the work of Lasnitzki and her collaborators in the mouse two decades earlier. In organ culture of human prostates, one sees a rapid increase in epithelial cells and decrease in stromal cells during the first 3-5 days of culture. While modulation of many phenotypic properties occurs, these cultures provide a simple and rapid way to achieve large numbers of human prostatic epithelial cells in cultured tissues that are markedly depleted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…The low level of enzyme activity in organ culture may be of interest in light of the changes that occurred in prostate tissue over time in culture. These included a proliferative response in the basal epithelial cell population and a concomitant loss of the malignant component (Schrodt and Foreman, 1971;Geller et al, 1992;Nevalainen et al, 1993;Pretlow et al, 1995;Varani et al, 1999; as well as the present report). The present study also demonstrated migration of the proliferating epithelial cells out from the gland across the surface of the tissue.…”
Section: Discussionsupporting
confidence: 51%
“…The low level of enzyme activity in organ culture may be of interest in light of the changes that occurred in prostate tissue over time in culture. These included a proliferative response in the basal epithelial cell population and a concomitant loss of the malignant component (Schrodt and Foreman, 1971;Geller et al, 1992;Nevalainen et al, 1993;Pretlow et al, 1995;Varani et al, 1999; as well as the present report). The present study also demonstrated migration of the proliferating epithelial cells out from the gland across the surface of the tissue.…”
Section: Discussionsupporting
confidence: 51%
“…1A). This method was selected for two key reasons: firstly, the use of a substrate for explant culture prevents cellular outgrowth that is frequently observed when tissues are cultured without support and completely submerged in media (Pretlow et al, 1995;Varani et al, 1999); secondly, the gelatin sponge used in this study is a commercial medical device developed for hemostasis (Ferrosan, 2014) that is readily available, cost-effective, and simple to use, making the method feasible for widespread adoption in translational cancer research laboratories. Figure 1A illustrates the PDE method using prostate tumors as an example.…”
Section: Pde Culture Of Solid Tumorsmentioning
confidence: 99%
“…(2013). Despite this long‐standing history and general acknowledgment of the potential of ex vivo cultured tissues to increase the clinical relevance of laboratory research (Centenera et al ., 2013; Kim, 2005; Pretlow et al ., 1995; Risbridger et al ., 2018; Vescio et al ., 1991), the PDE method has not been widely adopted to study solid tumors. The purpose of this study was to highlight advantages of the PDE model and demonstrate how it can be applied to interrogate hormone‐dependent cancers such as those of the breast and prostate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, for a cultured tumor to be representative of actual cancer, it is essential that the tumor, as it proliferates in vitro, maintains its tissue organization and structure, its oncogenic properties, its differentiated functions, and any cellular heterogeneity present in vivo. All these requirements are fulfilled by prostate organ culture [13][14][15]. By adding lymphocyte stimuli in the culture medium, it is therefore possible to analyze T cell responsiveness in normal or tumor tissues (Fig.…”
mentioning
confidence: 99%